Central Compartment Involvement in T3 & T4 Papillary Thyroid Carcinoma (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Lymphatic metastasis in papillary thyroid cancer (PTC) is common; however, the extent of central compartment lymph nodes dissection (CCD) is controversial and requires the knowledge of pattern for central compartment (level VI) lymph nodes metastasis (CCM).Objective: To determine the frequency of central compartment (level VI) lymph node metastasis in T3 & T4 papillary thyroid carcinoma.Methods: This study was conducted in the Department of Otolaryngology-Head &Neck Surgery, BSMMU, Dhaka, from January 2019 to June 2020. A total of 31 cases of T3 & T4 PTC were selected after obtaining clearance and approval from the IRB of BSMMU; the subjects were included based on the inclusion and exclusion criteria. After taking informed written consent detailed history and examination was done. Ultrasound neck and fine-needle aspiration cytology was taken from all thyroid swelling. All patients had underwent total thyroidectomy with central compartment dissection. The data were analyzed by computer-based statistical software SPSS version 26. Results were expressed as frequency and percentage. Z proportion test was done as applicable.Results: In this study, mean (±SD) tumor size was 3.66 (±1.34) cm. 20 (64.52%) had T3 and 11 (35.48%) T4 PTC. 11 (35.48%) had N0, 20 (64.52%) N1a and 8 (25.81%) N1b. 20 (64.52%) had overall central compartment lymph nodes metastasis. Among T3 papillary thyroid carcinoma, 12 (60%) had overall central compartment lymph nodes metastasis, and inT4 papillary thyroid carcinoma, 8 (72.7%) had overall central compartment lymph nodes metastasis. This difference was not statistically significant.Conclusion: The frequency of central compartment (level VI) lymph node metastasis (CCM) is high (64.52%) in T3 & T4 papillary thyroid carcinoma. So central compartment (level VI) should be dissected in advanced (T3 & T4) papillary thyroid carcinoma.Bangladesh J Otorhinolaryngol 2022; 28(2): 149-156